Organic compost and wastewater on the initial growth of oilseed plants - Júlia S. Pereira; Jean P. Guimarães; Riuzuani M. B. P. Lopes; Maria S. S. de Farias; Vera L. A. de Lima; Carlos A. V. de Azevedo (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The study was conducted in two experiments in greenhouse of the CTRN/UFCG, aiming to evaluate the use of organic compost from household garbage and irrigation with treated domestic wastewater on the growth of castor bean 'BRS-188/Paraguaçu' and sunflower 'Embrapa 122-V2000'. Both experiments were conducted a randomized block design in 6 x 2 factorial scheme, with three replicates, which corresponded to six doses of organic compost (0, 1.2, 2.0, 2.8, 3.6 and 4.4 kg pot-1, equivalent to 0, 60, 100, 140, 180 and 220 kg N ha-1) and two types of water (freshwater and wastewater). It was found that the organic compost doses significantly influenced the growth of sunflower and castor bean in all evaluations, except for stem diameter. The maximum plant heights were 91.7 cm for castor bean and 85.2 cm for sunflower at the doses of 180 and 220 kg N ha-1, respectively. The highest values of number of leaves were obtained for the N dose of 220 kg ha-1 in both crops. The influence of wastewater on growth variables was only observed in the final evaluations, for both sunflower and castor bean.